Pola Rencana Penanganan Air Limbah Domestik Pemukiman Kumuh Perkotaan di Kabupaten Lampung Utara - Ismadi Raharjo (Jurnal Ilmiah Teknik Pertanian - TekTan, 2015)
Urban Slum in North Lampung District according to a decree contained in 14 locations located in 4 Districts. Among the 14 locations there are 10 locations of slum on the edge of the river (inhabited by about 700 families) in North Lampung district estimated directly discharge wastewater into rivers results of their activities (times) Uban and Rarem Way. This may give a negative impact on the aquatic environment in the two rivers for daily flow of waste water flow rate of about 35,000 liters with a load of BOD (Biologycal Oxygen Demand) approximately 18.76 kg. It is necessary for the direction of domestic waste water treatment patterns construct Waste Treatment Plant (WWTP) for communal housing residents around the two rivers. Each communal WWTP will serve five families or about 25 residents of the dwelling. In consideration of the position of residential location, the communal formed on communal distinguished which is right by the river and the communal were about 25-50 m from the river. In the treatment of domestic waste water in communal needs to be established septic tank to treat sewerage of toilets (WC) is equipped with a biofilter combination of anaerobic-aerobic (to treat black water processed from the sewage and gray water from waste water non toilet) with a capacity of 2000 liters of water of waste per day, the residence time of about 1.69 days, and the ability of polluters BOD allowance of about 80%. WWTP construction standards biofilter used is concrete construction size: effective length of 225 cm, 100 cm effective width, volume cavity biofilter media types bioball 0.70 m3, and equipped with hiblow 40 liters / minute andÂ  circulation pump of 24 watts for the aerobic process.Â Keywords: domestic waste water, slums, WWTP biofilter communal